Dosimetric accuracy assessment of a treatment plan verification system for scanned proton beam radiotherapy: one-year experimental results and Monte Carlo analysis of the involved uncertainties - Molinelli, Silvia; Mairani, A.; Mirandola, A.; Freixas, G. Vilches; Tessonnier, T.; Giordanengo, S.; Parodi, Katia; Ciocca, M.; Orecchia, R. (Physics in medicine and biology, 2013)
During one year of clinical activity at the Italian National Center for Oncological Hadron Therapy 31 patients were treated with actively scanned proton beams. Results of patient-specific quality assurance procedures are presented here which assess the accuracy of a three-dimensional dose verification technique with the simultaneous use of multiple small-volume ionization chambers. To investigate critical cases of major deviations between treatment planning system (TPS) calculated and measured data points, a Monte Carlo (MC) simulation tool was implemented for plan verification in water. Starting from MC results, the impact of dose calculation, dose delivery and measurement set-up uncertainties on plan verification results was analyzed. All resulting patient-specific quality checks were within the acceptance threshold, which was set at 5% for both mean deviation between measured and calculated doses and standard deviation. The mean deviation between TPS dose calculation and measurement was less than ±3% in 86% of the cases. When all three sources of uncertainty were accounted for, simulated data sets showed a high level of agreement, with mean and maximum absolute deviation lower than 2.5% and 5%, respectively.